The Design of IoT-based Business Process for SME Digital Transformation: a Case of Unofficial Car Service Workshop - Widjaja, Albertus Hendrawan; Gunawan, Gunawan (Journal of Applied Data Sciences, 2024)
The Internet of Things (IoT) offers innovation processes that transform industry, finance, healthcare, agriculture, hospitality, and other sectors through process automation. Integrating IoT into business processes will transform an organization for better time, cost efficiency, and customer satisfaction. While the advantages of adopting IoT in the business process are widespread, the clear guidelines for implementing IoT for SMEs are limited. SMEs often do not recognize the potential of digital transformation and do not receive the necessary assistance to undertake critical development activities. This paper addresses this issue by focusing on IoT solutions for a car service workshop as an SME. This study aims to analyze the current business processes and design an IoT-based business process model for a car service workshop. The system development life cycle was adopted partially to design IoT-based business processes. The proposed business process model is designed with Business Process Modeling Notation (BPMN) to minimize time, effort, and cost inefficiencies. The concept and design of IoT systems were validated by the manager of five car service workshops. They perceived the transformation of car service using IoT as innovative, potentially increasing their business competitiveness. The respondents suggested that the implementation was executed gradually because of human resource readiness and investment costs. The design of IoT-based business process could become the guideline for car service workshops to transform the business into Industry 4.0.